Apakah Inovasi Hijau Dan Pengungkapan Emisi Karbon Dapat Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur? - Harvinna Dwi Putri; Henri Agustin (Jurnal Akademi Akuntansi, 2023)
The development of the industrial world is currently very competitive with each other, including industries in Indonesia. In addition, developments can cause environmental damage as a result of the company's activities. Therefore, this might have a negative impact on society and lower the company’s worth. The study aims to investigate to link between firm value and green product innovation, green process innovation, and disclosure of carbon emissions. Using purposive sampling criteria, the research sample consisted of manufacturing companies listed on the Indonesia Stock Exchange listed in the PROPER rating from 2017 to 2020, and combined into 30 companies with 115 observations. According to legitimacy, signaling, and stakeholder theory, the study’s findings show that green process innovation and disclosure of carbon emissions have a positive influence on firm value. This shows that manufacturing companies have succeeded in reducing the impact of their activities on the environment and have complied with environmental regulations. Meanwhile, green product innovation has a negative effect on firm value, this is because the participation of manufacturing companies in Indonesia in implementing green product innovation is still low. This research contributes to theory and practice in companies that want to produce environmentally friendly products. The results of these findings can be a reference for investors in making decisions.